Silicon increases chlorophyll and photosynthesis and improves height and NDVI of cotton (Gossypium hirsutum L. r. latifolium Hutch) (Research, Society and Development, 2020)
Silicon (Si) it is a beneficial element that relieves biotic and abiotic stresses in plants. However, cotton plants are not considered Si accumulators, with low potential for uptake the element by roots. The objective of this study was to evaluate the effect of combinations of Si rates applied by leaf spray and soil on the physiology, growth and yield of cotton (Gossypium hirsutum L. r. latifolium Hutch). The experimental design was a randomized complete block in a 3 x 4 factorial scheme with four replications. Leaf spraying consisted of three Si concentrations (0, 500, and 1000 mL ha-1) corresponding to 0, 100, and 200 ml ha-1 of monosilicic acid, with spraying split into three applications at stages V4, V6 and V8. Soil-based fertilization consisted of four Si rates in (0, 2.5, 5.0, and 10.0 kg ha-1) corresponding to 0, 0.5, 1.0, and 2.0 kg ha-1 of SiO2. At flowering, photosynthesis, green color index (GCI), plant height, and NDVI were evaluated. The application of Si in the planting furrow near the rhizosphere increased the green color index, reflecting a gain in photosynthesis and plant height, which positively increased NDVI. The use of high solubility Si in the planting furrow can increase the concentration of monosilicic acid in the area with the highest root distribution, enhancing the effect of this element in a non-accumulator crop such as cotton, by improving the green color index, photosynthesis and hence reflecting on gains in plant height and plant leaf area demonstrated by NDVI.